Metagenomic investigation of bacterial community of arsenic-prone area in the northwest region of Bangladesh - Rahman, Khondaker Md Jaminur; Diba, Farzana; Shuvo, Md Sadikur Rahman; Siddique, Mohammad Anwar; Hossain, M Anwar; Sultana, Munawar (Bangladesh Journal of Microbiology, 2023)
Metagenomic analysis provides in-depth understanding of microbe mediated Arsenic (As) metabolism. The present study aims atmetagenomic analysis of the distribution, diversity, and abundance of bacteriome in arsenic affected groundwater and surrounding soils collected fromBogra district of Bangladesh. Metagenomic DNA was extracted from two groundwater samples BCW3 andBCW4 (As content10μgL-1 and 500 μgL-1, respectively), and two tube-well surrounding soil samples BSS1 and BCS5 (As content335 μgkg-1 and 492 μgkg-1),where As rich water flows off. Metagenomic analysis of six hypervariable regions of 16S rRNA gene resulted in a total of 788709 processed sequence reads and 5878 operational taxonomic units (OTUs). Bacterial richness, abundance and diversity (alpha and beta) were higher in BCW4 (85 genera) than BCW3 (19 genera) whereas both soil samples exhibited almost similar richness and diversity. Predominant genera in BCW3 were Pseudomonas, Microbacterium, Achromobacterwhereas Acinetobacter, Thiothrix, Stenotrophomonas, Paracoccus, Dechloromonas dominated in BCW4. Soils were co-dominated with more than hundreds of genera with a high relative abundance of Bacillus, Rhodoplanesand Pseudomonas.Metagenomic investigation explored potentialarsenotrophicbacteriome. Exploring microbial community might help to understand the biogeochemistry of As affected groundwater and surrounding soil environment. Bangladesh J Microbiol, Volume 39, Number 1, June 2022, pp 31-38